Update to the Treatment of Parkinson’s Disease Based on the Gut-Brain Axis Mechanism - Sun, Xiaohui; Xue, Li; Wang, Zechen; Xie, Anmu (Frontiers in Neuroscience, 2022)
Gastrointestinal symptoms represented by constipation were significant non-motor symptoms of Parkinson's disease and were considered early manifestations and aggravating factors of the disease. This paper reviewed the research progress of the mechanism of the gut-brain axis in Parkinson's disease and discussed the roles of α-synuclein, gut microbiota, immune inflammation, neuroendocrine, mitochondrial autophagy, and environmental toxins in the mechanism of the gut-brain axis in Parkinson's disease. Treatment of Parkinson's disease based on the gut-brain axis theory has also been discussed, including ① dietary therapy, such as probiotics, vitamin therapy, Mediterranean diet, and low-calorie diet, ② exercise therapy, ③ drug therapy, including antibiotics; gastrointestinal peptides; gastrointestinal motility agents, and ④ fecal flora transplantation can improve the flora. ⑤Vagotomy and appendectomy were associated but not recommended.